The Experimental Activities: a methodological strategy in the significant learning of Chemistry - Garaicoa Flores , Briggitte Dennisse; Zambrano Muñoz , Mavelyn Jailine (Revista Minerva, 2022)
Chemistry is one of the subjects that needs to have a close relationship between theory and practice, so a theory class is not enough, because significant learning is not encouraged, so the objective of this The work is to compile information on how the experimental laboratory activities and the different learning methods drastically influence the affordability of meaningful learning and, above all, how they promote the improvement of the cognitive activity of said subject in each of the students, either in a virtual or face-to-face system. The methodology applied in this study is inferred from a bibliographical research which is based on the theoretical foundations based on previous studies carried out by contemporary authors who have expressed their position on the variables of this article and their importance in education indefinitely. It is inferred that the comprehensive training of students can be strengthened through methodological strategies that are consistent with each content and thus promote meaningful learning supported by appropriate tools that enable this process.
Keywords: Laboratory experimental activities; methodological strategies; meaningful learning